Correlation study between microstructure and fluidity of molten slag during co-gasification of coal and indirect coal liquefaction residue: Molecular dynamics simulation. (15th October 2022) - Zhang, Linmin; Wei, Juntao; Bai, Yonghui; Song, Xudong; Wang, Jiaofei; Su, Weiguang; Lv, Peng; Zhou, Ying; Nai, Guoxing; Yu, Guangsuo
Graphical abstract: Highlights: Viscosity behavior during co-gasification of ICLR and coal was explored by MD simulation. ICLR addition could significantly reduce the complexity and polymerization of slag. FeO was the main component that causes changes in viscosity and microstructure. Changing of macroscopic viscosity was closely related to evolution of microstructure. This study could provide theoretical support for the resource utilization of solid waste. Abstract: Co-gasification of indirect coal liquefaction residues (ICLR) and coal is an effective way to achieve harmless and sustainable treatment of hazardous wastes. The long-term and stable operation of a co-gasification largely depends on the flow behavior of coal-ash slag. Herein, classical molecular dynamics simulation (MD) and Raman spectroscopy were used to study the microstructure of slag and its relationship with viscosity during the co-gasification of ICLR and coal. The results showed that with the addition of ICLR, the viscosity of slag decreased continuously. This reduction in viscosity was attributed to the increase of FeO content in the system with the addition of ICLR. As a network modifier, FeO could easily provide O 2− at high temperatures, thereby destroying bridge oxygen and converting more tricluster oxygen and bridge oxygen into non-bridge oxygen. This significantly reduced the structure complexity and polymerization degree of slag, thereby reducing its viscosity. Finally, the correlation between the microstructural and viscosity was further analyzed. It was found that there was a quadratic function relationship between Q 4 proportion and viscosity, and the formula was μ = 0.025(Q 4 ) 2 -Q 4 + 12.03. The purpose of this work was to provide theoretical support for slag flow mechanisms during the gasifier slagging-tapping process and the resource treatment of hazardous wastes.